PROBLEMS AND DEVELOPMENT PROSPECTS OF THE LEGAL CLINIC IN THE HIGHER EDUCATION SYSTEM - Baghdasaryan, Tehmine; Khechoyan, Ani (Bulletin of Yerevan University C: Jurisprudence, 2026)
The relevance of the research is determined by the problems of legal clinic activities and the need to introduce effective mechanisms aimed at overcoming them in the higher education system, which can be based on the best practices of European legal clinics, which were studied in this research.The purpose of the research is to identify the problems related to the activities of legal clinics and propose mechanisms aimed at solving them in the context of the prospective development of legal clinical education in the Republic of Armenia.The authors' results of the research lead to the substantiation of the hypotheses put forward in the introduction of the research, that:1. legal clinical courses in the RA universities should be mandatory in the curriculum for motivating more students to get involved in the activities of the clinic,2. legal clinics of universities should receive financial or other support from the state, which will strengthen the relationship between the state and the higher educational institutions. The theoretical results of the research can be used in the theoretical studies dedicated to the problems of legal clinical education, as well as in the process of improving the legislation regarding the legal clinics in the system of higher education of RA.
Keywords: legal clinical education; free legal aid; vulnerable groups of the society; Simulation Clinics; Externship-Oriented Clinics; Street Law clinics; access to justice